PENGARUH MODEL BRAIN BASED LEARNING (BBL) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI COLOMADU TAHUN PELAJARAN 2012/2013 - Saparina, Riska; Santosa, Slamet; Ariyanto, Joko (Universitas Sebelas Maret, 2015)
The aim of this research is to know the influence of brain based learning (BBL) model toward biology learning achievement of X degree students at SMA Negeri Colomadu in academic year 2012/2013.This research was a quasi experiment research using posttest only non equivalent group design. This research applied BBL model in experimental group and deduktif approach with discussion, classical course and question-answer method in control group. The population of this research was all of X degree students at SMA Negeri Colomadu in 2011/2012 academic year. Sampling techniques used cluster sampling, that has chosen X4 as experiment group and X5 as control group. Data was collected using multiple choice test, observation sheet, and document. The data were analyzed by t-test. This research concluded that the application of BBL model has taken good effect toward student’s achievement cognitive, psychomotor, and affective domain in learning biology of SMA Negeri Colomadu. Keywords: Brain Based Learning Model, Biology Learning Achievement.